(untitled) (Communications in Computational Physics, 2020)
Converting subsurface offset domain common image gathers (ODCIGs) to angle domain common image gathers (ADCIGs) through a Radon Transform (RT) in either the spatial or wavenumber domain is efficient and valid except for the distortion of both frequency spectrum and amplitude versus angle (AVA) effect. This paper presents two modifications to the existing method to keep the frequency spectrum of the resultant ADCIGs the same as the input data and to preserve the relative amplitudes. The spectrum invariance is achieved by replacing the conventional RT or slant slack by an invertible RT. Amplitude preservation is obtained by applying an amplitude correction factor in the angle domain. Tests on both synthetic and field datasets validate the accuracy of these modifications.